The experience of employment strain and activation among temporary agency workers in Canada. Issue 1 (1st January 2017) - Bosmans, Kim; Lewchuk, Wayne; De Cuyper, Nele; Hardonk, Stefan; Van Aerden, Karen; Vanroelen, Christophe
ABSTRACT: This article integrates the employment strain model with the social stress model in order to reveal the mechanisms that explain the relation between precarious employment and mental well-being. This model is applied to the case of temporary agency employment by analysing 41 in-depth interviews with temporary agency workers from Canada. The results show how temporary agency workers perceive employment-related uncertainties and efforts mainly as negative and to a lesser extent as positive experiences, respectively evoking strain or activation. Further, it is revealed how uncertainties and efforts mutually reinforce each other, which increases strain, and how support can serve as a buffer.